No irrelevant Jesus: on Jesus and the church today - Lohfink, Gerhard (A Michael Glazier book, 2014)
"A Michael Glazier book.". - Translation of: Gegen die Verharmlosung Jesu. Freiburg im Breisgau: Verlag Herder GmbH, 2013.. - Includes bibliographical references (pages 315-321) and indexes.. - On not taming Jesus -- Jesus revolutionizes linear time -- How will the hungry be filled in the reign of God? -- How did Jesus heal? -- What does the Love Commandment mean? -- No place for warriors in the name of God -- Did Jesus die for "many" or for "all"? -- How could an individual redeem the whole world? -- Jesus and the shattered people of God -- The canon and the many confessions -- Some irenic thoughts on the episcopacy and the primacy -- Must the pope be conservative? -- What constitutes the church's "newness"? -- The church's proper name is "assembly" -- The unknown Paul -- How a sacrament works -- A catastrophe in the life of David -- On the sense and nonsense of good intentions -- Has the church been deprived of fasting? -- Prayer as access to reality -- What distinguishes Christianity from the religions? -- Where do we get our "values"? -- The Magnificat: signal for a revolution -- Faith: how does it work? -- The Bible in my life as an exegete.